2023
DOI: 10.1002/advs.202304294
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for Diagnosis and Treatment of Atherosclerosis

Jingyun Cheng,
Hui Huang,
Yu Chen
et al.

Abstract: With the changing disease spectrum, atherosclerosis has become increasingly prevalent worldwide and the associated diseases have emerged as the leading cause of death. Due to their fascinating physical, chemical, and biological characteristics, nanomaterials are regarded as a promising tool to tackle enormous challenges in medicine. The emerging discipline of nanomedicine has filled a huge application gap in the atherosclerotic field, ushering a new generation of diagnosis and treatment strategies. Herein, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 399 publications
0
2
0
Order By: Relevance
“…We hope that these findings provide valuable references for future research and inspire further exploration and expansion in this field by scholars. the sublimation vapor pressure of the solid q eff an effective heat flux R universal gas constant, generally equal to 8.314 (J kg −1 K −1 ) R 2 Correlation coefficient RMSE root mean squared error t time (s)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that these findings provide valuable references for future research and inspire further exploration and expansion in this field by scholars. the sublimation vapor pressure of the solid q eff an effective heat flux R universal gas constant, generally equal to 8.314 (J kg −1 K −1 ) R 2 Correlation coefficient RMSE root mean squared error t time (s)…”
Section: Discussionmentioning
confidence: 99%
“…According to current definitions, nanomedicines are nanoscale tools utilized for disease diagnosis, prevention, and treatment [1,2]. They have the capacity to facilitate early disease detection and prevention, direct a bioactive molecule to the intended site of action, and regulate the release of the molecule to guarantee an ideal concentration at the target of therapy for the intended duration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These NPs, often composed of biocompatible metals such as gold, silver, or iron, offer unique properties that enable precise drug delivery to affected areas while minimizing systemic side effects. For instance, studies by Cheng et al revealed the successful application of gold NPs for delivering anti-inflammatory agents to atherosclerotic plaques and tomography imaging of atherosclerosis [ 172 ]. Recent research by Mao et al and Wang et al highlighted the efficacy of a bioresorbable magnesium alloy stent coated with an anti-proliferative drug, offering a dual benefit of mechanical support and localized drug release, leading to improved outcomes in atherosclerosis treatment [ 173 174 ].…”
Section: Reviewmentioning
confidence: 99%
“…12,13 Given its severe morbidity and mortality globally, comprehensive investigations of AS have garnered great scientific interest, and there is a strong demand for strategies capable of thoroughly studying AS, aiming to reveal more critical pathogenetic mechanisms, develop more accurate diagnostic methods, establish more practical therapeutic treatments and discover more effective drugs, that can alleviate symptom and decrease the overall risk of deaths of AS. 14–16…”
Section: Introductionmentioning
confidence: 99%